Directive forms Expressed by Male and Female Respondents in Different Situational Contexts - Gavenila, Euodia Inge; Arsa, Yohanes; Pasaribu, Truly Almendo (Humaniora, 2019)
This research intended to explore the relationship between language and gender by answering two research questions. First, it was how male and female respondents expressed directive forms. Second, it was what the social factors that influenced the choice of directive forms were. The two issues were considered urgent because gender was a variable that determined how people used language, including directive forms. Data were collected by distributing offline open-ended questionnaires to 18 students from the 2015-2017 batch of the English Language Education Study Program (ELESP) of Sanata Dharma University. The results show that to some extent females and males express directive forms differently. Men tend to be direct in expressing directive messages, while women use interrogative and declarative forms in delivering the messages since these forms are considered as more polite and less direct. Women tend to save their faces by using more indirect or polite forms because they avoid being considered impolite. Then, social class, the relationship between participants, and formality alsoinfluence the use of directive forms.